Exposure to fire smoke in fire training structures: A prospective observational study. Issue 7 (9th August 2022) - Allonneau, Alexandre; Mercier, Samuel; Rieunier, Fanny; Menguy-Fleuriot, Anne; Louyot, Catherine; Duvollet, Marc; Burlaton, Guillaume; Nicolas, Anne; Jouffroy, Romain; Prunet, Bertrand
Abstract: The aim of this study was to assess the level of exposure to and contamination by smoke within a population of firefighter instructors. We performed a prospective observational study from September 17 to September 26, 2018, using environmental samples and urinary biomarker analysis. Occupational exposure limits (OELs) were never exceeded, except for carbon monoxide for the fire attack training chamber and formaldehyde and carbon monoxide for the fire box. As regards to urinary biomarkers, we observed that 1OHP and 1-naphtol did accumulate. The pre-post analysis showed an acute exposure exceeding the BRVs of benzene, 1-hydroxypyrene and naphtol, except for 3-benzo[a]pyrene which was undetectable in half of the cases. Even if values were reassuring, an effort could be made to improve the working conditions and reduce contamination by rethinking the respiratory protection and improving PPE quality.